Evolution of the superconducting properties from binary to ternary APC-Nb3Sn wires. (4th February 2021) - Ortino, M; Pfeiffer, S; Baumgartner, T; Sumption, M; Bernardi, J; Xu, X; Eisterer, M
Abstract: We present a study conducted on binary Tube Type and ternary powder-in-tube Nb3 Sn wires manufactured using the artificial pinning centres-internal oxidation method. All the specimens are doped with Zr: oxide nano-particles of this element are responsible for the pinning improvement, both by refining the A-15 grain-size and their own point-pinning contribution. Low-field J c   magnetometry confirms that the hadron-hadron Future Circular Collider (FCC-hh) specifications are met by one ternary doped-sample. The differences in microstructure were assessed by scanning electron microscopy/transmission electron microscopy to clarify the reasons for the pinning improvement between the two generations. The deviations from the Dew Hughes model are also discussed, underlying some non-linear addition due to competition between the two pinning mechanisms. Finally, we show how the introduction of Ta as a ternary addition influences the A-15 phase by focusing on the radial inhomogeneities, evaluating the T c   distribution and Sn composition gradients. The latter are used to model the currents, enabling us to evaluate the individual weights of the pinning mechanisms and their absolute contributions at the High Luminosity-Large Hadron Collider and FCC-hh dipoles operational points.